Phytohaemagglutinin's effect on Neospora caninum antigen production - Kikuti, Mariana [UNESP]; Richini-Pereira, Virgínia Bodelão [UNESP]; da Silva, Rodrigo Costa [UNESP]; Langoni, Hélio [UNESP] (My University, 2013)
The parasite Neospora caninum affects mainly cattle and dogs. This study aimed to evaluate the effect of phytohaemagglutinin (PHE) in antigen production of N. caninum NC-1 strain in gerbils (Meriones unguiculatus) and in vitro. 20 gerbils were used, 10 inoculated intraperitoneally with 1 × 106 tachyzoites and 10 with 1 × 106 tachyzoites plus 300 μL/mL of PHE. 16 bottles of Vero cell culture were inoculated, 8 with 1.5 × 105 tachyzoites and 8 with 1.5 × 105 tachyzoites plus 30 μL/mL of PHE. Serology of gerbils was performed on day 0 and before euthanasia. Tachyzoites present in peritoneal fluid and cell culture bottles were quantified by Neubauer chamber and by real-time PCR (qPCR). PHE has not interfered in the production of tachyzoites of N. caninum in intraperitoneal inoculated gerbils and the effect of PHE in cell culture had a negative impact, considering the qPCR technique as the gold standard.
Keywords: Cell culture; Gerbil; Neospora caninum